Larotrectinib in patients with TRK fusion-positive solid tumours: a pooled analysis of three phase 1/2 clinical trials. Issue 4 (April 2020) - Hong, David S; DuBois, Steven G; Kummar, Shivaani; Farago, Anna F; Albert, Catherine M; Rohrberg, Kristoffer S; van Tilburg, Cornelis M; Nagasubramanian, Ramamoorthy; Berlin, Jordan D; Federman, Noah; Mascarenhas, Leo; Geoerger, Birgit; et al.
Summary: Background: The selective TRK inhibitor larotrectinib was approved for paediatric and adult patients with advanced TRK fusion-positive solid tumours based on a primary analysis set of 55 patients. The aim of our analysis was to explore the efficacy and long-term safety of larotrectinib in a larger population of patients with TRK fusion-positive solid tumours. Methods: Patients were enrolled and treated in a phase 1 adult, a phase 1/2 paediatric, or a phase 2 adolescent and adult trial. Some eligibility criteria differed between these studies. For this pooled analysis, eligible patients were aged 1 month or older, with a locally advanced or metastatic non-CNS primary, TRK fusion-positive solid tumour, who had received standard therapy previously if available. This analysis set includes the 55 patients on which approval of larotrectinib was based. Larotrectinib was administered orally (capsule or liquid formulation), on a continuous 28-day schedule, to adults mostly at a dose of 100 mg twice daily, and to paediatric patients mostly at a dose of 100 mg/m 2 (maximum of 100 mg) twice daily. The primary endpoint was objective response as assessed by local investigators in an intention-to-treat analysis. Contributing trials are registered with ClinicalTrials.gov, NCT02122913 (active not recruiting), NCT02637687 (recruiting), and NCT02576431 (recruiting). Findings: Between May 1, 2014, and Feb 19, 2019, 159 patients with TRK fusion-positive cancer were enrolled and treated with larotrectinib. Ages ranged from less than 1 month to 84 years. The proportion of patients with an objective response according to investigator assessment was 121 (79%, 95% CI 72–85) of 153 evaluable patients, with 24 (16%) having complete responses. In a safety population of 260 patients treated regardless of TRK fusion status, the most common grade 3 or 4 larotrectinib-related adverse events were increased alanine aminotransferase (eight [3%] of 260 patients), anaemia (six, 2%), and decreased neutrophil count (five [2%]). The most common larotrectinib-related serious adverse events were increased alanine aminotransferase (two [<1%] of 260 patients), increased aspartate aminotransferase (two [<1%]), and nausea (two [<1%]). No treatment-related deaths occurred. Interpretation: These data confirm that TRK fusions define a unique molecular subgroup of advanced solid tumours for which larotrectinib is highly active. Safety data indicate that long-term administration of larotrectinib is feasible. Funding: Bayer and Loxo Oncology.